PENGARUH DEBT TO EQUITY RATIO DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN - Jeni Irnawati; Hadijah Febriana; Deni Yuli Asmita (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Growth Opportunity to Firm Value either partially or simultaneously. The method used in this study is a quantitative method by taking data from the Financial Statements. Data analysis used descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, correlation coefficient test and coefficient of determination. The results showed that there was a significant effect between the Debt to Equity Ratio on the Firm Value (PBV). As evidenced by the tcount values of 3.112 > ttable and 1.89458, the debt to equity ratio had a significant effect on firm value. Growth opportunities have a significant effect on firm with tcount 2.433 > ttable 1.89458.